ANALISIS PENGARUH MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KUALITAS KERJA KARYAWAN DI KSPPS HARAPAN UMAT PATI - Mukti Mukti; Siti Rochmah; Fidyah Yuli Ernawati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract The purpose of this study was to determine the effect of work motivation and organizational commitment on the employees of KSPPS Harapan Ummah Pati. The population in this study were all 64 people of KSPPS Harapan Ummah Pati employees. The total sample is 64 respondents. The variables in this study are motivation (X1), organizational commitment (X2) and employee work quality (Y). Methods of data collection using a questionnaire. The analytical method used: classic assumption test which consists of normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. Multiple regression analysis, t test, F test (Fairness Test Model / Goodness Of Fit Model), test the coefficient of determination (R2), The results of this study are: 1). Motivation has an effect on the quality of work of KSPPS Harapan Ummah Pati employees. The test results show the t arithmetic value of 2.541, and using a significance limit of 0.05, while t table n = 64 is 1.998, then t arithmetic 2.541 > t table 1.998, which means that the hypothesis in this study is accepted, significant < 0.05 or (0.002 < 0.05). Thus it can be interpreted that there is a positive influence of motivation on the quality of employee work. 2) Organizational commitment has an effect on the quality of work of KSPPS Harapan Ummah Pati employees. The test results show the t-count value is 2.952 and uses a significance limit of 0.05, while t-table n = 64 is 1.998, then t-count is 1.952 > t-table is 1.998, which means that the hypothesis in this study is accepted, significant <0.05 or ( 0.002 < 0.05). Thus it can be interpreted that there is a positive influence of organizational commitment on the quality of employee work. The suggestions given are: 1) Leaders of KSPPS Harapan Ummah Pati should motivate their employees to work by providing welfare assistance, providing a sense of security, encouraging employees to interact with each other and work together between subordinates and superiors and fellow co-workers, giving awards 2) Leaders of KSPPS Harapan employees The Pati people should pay more attention to the organization's commitment to employees, because some employees still feel that their work needs have not been fulfilled, and the leadership of the organization to be further improved, instilling in their hearts that employees will lose if they leave the organization